2021
DOI: 10.1021/acsapm.1c01435
|View full text |Cite
|
Sign up to set email alerts
|

Highly Aligned Electrospun Polymer Fibers Produced Using a Corrugated Static Collector

Abstract: Fiber alignment via electrospinning is a challenging process that requires complex optimization because of the synergistic contribution of the solution, processing, and environmental parameters. Much of the work has focused on the design of collectors that enable fiber alignment, in contrast to that of the stationary, flat collector where randomly oriented fibers are deposited. However, in most cases, the proposed collectors have either movable parts or complicated configurations. The present study focuses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 71 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…51,52 We have recently reported the fabrication and characterization of highly aligned electrospun P3HTrich electrospun fibrous systems (i.e., P3HT/PEO wt.%, 80:20; P3HT/PEO wt.%, 95:5) using a corrugated static collector. 53 Based on our previous knowledge regarding the experimental parameters for processing P3HT/ PEO polymer solutions, in this study, the optimum electrospinning conditions were facilely defined, resulting in P3HT/PEO and P3HT/PEO/CsPbBr 3 electrospun fibrous mats (see supplementary Figure S1).…”
Section: Fabrication and Morphological Characterization Of Electrospu...mentioning
confidence: 99%
“…51,52 We have recently reported the fabrication and characterization of highly aligned electrospun P3HTrich electrospun fibrous systems (i.e., P3HT/PEO wt.%, 80:20; P3HT/PEO wt.%, 95:5) using a corrugated static collector. 53 Based on our previous knowledge regarding the experimental parameters for processing P3HT/ PEO polymer solutions, in this study, the optimum electrospinning conditions were facilely defined, resulting in P3HT/PEO and P3HT/PEO/CsPbBr 3 electrospun fibrous mats (see supplementary Figure S1).…”
Section: Fabrication and Morphological Characterization Of Electrospu...mentioning
confidence: 99%
“…15 Substantial research efforts have shown that the uniform electric field distribution can produce thinner and more uniform fibers. 16,17 At present, the strategies to improve the electric field distribution are mainly divided into three categories, containing the development of spinnerets, 18 the design of collectors, 19 and the addition of auxiliary electrodes. 20 Zhou et al 21 employed a flat plastic spinneret with a custom-made-three-hole instead of the conventional needles in the electrospinning system.…”
mentioning
confidence: 99%